Blinatumomab as frontline therapy for B-cell precursor acute lymphoblastic leukemia in a critically ill young adult: a case report - Mendez-Guerra, Carolina (2024)
Background: Adolescent and young adults (AYA) with acute lymphoblastic leukemia (ALL) represent a unique complex group, particularly, with respect to the therapeutic approach. The current trend is to treat AYAs with pediatric ALL treatment regimens, which has been associated with higher survival rates. Blinatumomab is a bispecific monoclonal antibody that binds to CD19 antigen on B-lymphoblasts and CD3 on T cells. Favorable outcomes regarding the utilization of blinatumomab have been obtained in both children and adults, for the treatment of relapsed/refractory (r/r) and minimal residual disease (MRD)-positive B-cell precursor ALL (B-ALL). Nevertheless, the safety and efficacy of blinatumomab in early stages of the disease as frontline therapy is not fully elucidated. Case Description: A 20-year-old male was referred to our hospital in critical condition for untreated newly diagnosed Philadelphia chromosome-negative B-ALL (Ph-negative B-ALL) complicated with sepsis and respiratory failure. After hemodynamic and ventilatory stabilization, induction therapy with blinatumomab as a continuous intravenous infusion was initiated followed by vincristine, daunorubicin and prednisone. Chemo-immunotherapy was well tolerated and by the end of induction, the patient improved his clinical status and achieved complete remission, with MRD negativity by bone marrow (BM) flow cytometry. Conclusions: Blinatumomab followed by chemotherapy showed favorable outcomes as frontline therapy in a newly diagnosed critically ill patient with Ph-negative B-ALL.